Year level, age, sex, mode of entry, and frequency of library use as correlates to the academic performance of BLIS students at U.P. Diliman - Lobo, Marie Joie A. (1998)
This study aims to determine the correlation of year level, age, sex, mode of entry and frequency of library use to the academic performance of BLIS students at U.P.